2020
DOI: 10.1002/lt.25759
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dual Hypothermic Oxygenated Machine Perfusion to Recover Extended Criteria Pediatric Liver Grafts

Abstract: The advent of machine perfusion is deeply changing the field of liver transplantation (LT), unveiling a spectrum of unexplored possibilities, both with hypothermic and normothermic perfusion. The renewed interest for these techniques originated from the necessity of improving preservation of grafts from extended criteria donors, which are now commonplace in everyday clinical practice. Hypothermic oxygenated machine perfusion (HOPE) has been associated with improved outcomes in grafts from donation after circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…A promising option, despite the limited experience in children, might be represented by ex vivo organ machine perfusion. 17,18 Thanks to machine perfusion, it is now possible to efficiently preserve a donated organ during complex surgical procedures, thus reducing the static cold ischemia time. 19,20 The possible advantages of delaying renal transplantation by 24-48 hours, when the liver graft should start functioning, thus preserving the kidney graft from excessive oxalate accumulation, 21,22 need to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A promising option, despite the limited experience in children, might be represented by ex vivo organ machine perfusion. 17,18 Thanks to machine perfusion, it is now possible to efficiently preserve a donated organ during complex surgical procedures, thus reducing the static cold ischemia time. 19,20 The possible advantages of delaying renal transplantation by 24-48 hours, when the liver graft should start functioning, thus preserving the kidney graft from excessive oxalate accumulation, 21,22 need to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…New perspectives are now opening for PH1 treatment. A promising option, despite the limited experience in children, might be represented by ex vivo organ machine perfusion 17,18 . Thanks to machine perfusion, it is now possible to efficiently preserve a donated organ during complex surgical procedures, thus reducing the static cold ischemia time 19,20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, limited evidence of machine perfusion implementation in the PLTx setting is available to date. The first report of a successful application of machine perfusion in the pediatric setting is dated 2019 and reported by Werner et al 46 , followed by the experience reported by the Turin group 47 . Indeed, PLTx requires a cautious approach, but once the benefits of machine perfusion will be ensured by multicenter studies, this technique would represent a valid support and eventually increase the PLTx donor pool.…”
Section: Setting the Stage Of Pltxmentioning
confidence: 99%